2004
DOI: 10.1094/cchem.2004.81.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of HMW Glutenins During Wheat Sourdough Fermentations

Abstract: Bakeries use sourdoughs to improve bread properties such as flavor and shelf life. The degradation of gluten proteins during fermentation may, however, crucially alter the gluten network formation. We observed changes that occurred in the HMW glutenins during wheat sourdough fermentations. As fermentation starters, we used either rye sourdough or pure cultures of lactobacilli and yeast. In addition, we incubated wheat flour (WF) in the presence of antibiotics under different pH conditions. The proteolytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
60
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 24 publications
9
60
2
1
Order By: Relevance
“…This is reflected by the considerable levels of maltose retrieved after each fermentation step and an increase of total amino acids upon fermentation (27,39,40,69). The present study showed that the competitiveness of sourdough LAB is enhanced by both the use of the arginine deiminase pathway (in an early stage) and the use of alternative electron acceptors.…”
Section: Discussionmentioning
confidence: 55%
“…This is reflected by the considerable levels of maltose retrieved after each fermentation step and an increase of total amino acids upon fermentation (27,39,40,69). The present study showed that the competitiveness of sourdough LAB is enhanced by both the use of the arginine deiminase pathway (in an early stage) and the use of alternative electron acceptors.…”
Section: Discussionmentioning
confidence: 55%
“…Second, proteolytic activity in aseptic doughs and sourdoughs was inhibited upon the addition of an aspartic protease inhibitor, indicating that cereal proteinases are responsible for the first step in gluten degradation. Aspartic protease inhibitors but not serine proteinase inhibitors were previously reported to inhibit proteolytic activities in sourdough extracts (22). Third, screening the genome of L. sanfranciscensis strain DSM 20451 did not provide evidence for a prt-like proteinase.…”
Section: Discussionmentioning
confidence: 88%
“…proteolytic activity in sourdough extracts is inhibited by aspartic protease inhibitors but not by serine protease inhibitors (22). Thus, the most active proteases in wheat sourdoughs are the cereal aspartic proteinases whereas serine proteinases from lactobacilli play a minor role only (34).…”
mentioning
confidence: 96%
“…In the present study, the focus was on processed breads, since food processing may alter the solubility of prolamins, e.g. the denaturation caused by heating decreases the solubility of the proteins, whereas the depolymerization of glutenins increases their solubility in aqueous alcohols (Loponen et al 2004). In addition, the formation of gluten network during mixing and baking induces changes in the extractability of wheat prolamins.…”
Section: Discussionmentioning
confidence: 99%